Multilayer electronic component
By introducing a silver (Ag) coating into the outer electrode of the multi-layer ceramic capacitor, a peeling structure is formed, and the problem of transfer of warping stress on the ceramic body is solved, thereby achieving the suppression of warping cracks and the improvement of mechanical strength.
Patent Information
- Application Number
- CN202411208348.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-06
- Filing Date
- 2024-08-30
- Publication Date
- 2025-03-07
AI Technical Summary
Multi-layer ceramic capacitors are prone to warping cracks during external impact, and the prior art is difficult to effectively suppress the transmission of warping stress to the ceramic body.
By introducing a silver (Ag) coating into the outer electrode, a peeling structure between the electrode layer and the conductive resin layer is formed to suppress the occurrence of warping cracks when warping stress is applied outside.
It effectively improves the warping stress of multi-layer electronic components, prevents the occurrence of warping cracks, and improves the mechanical strength of the components.
Smart Images

Figure CN119581220A_ABST
Abstract
Description
[0001] This application claims the benefit of priority from Korean Patent Application No. 10-2023-0118092 filed on September 6, 2023 in the Korean Intellectual Property Office, the disclosure of which is incorporated herein by reference in its entirety. Technical Field
[0002] The present disclosure relates to a multi-layer electronic assembly. Background Art
[0003] Multilayer ceramic capacitors (MLCCs, a type of multilayer electronic component) are chip capacitors mounted on printed circuit boards of various types of electronic products, such as image display devices including liquid crystal displays (LCDs) and plasma display panels (PDPs), computers, smart phones, and mobile phones, and are used to charge or discharge electricity therein.
[0004] Multilayer ceramic capacitors are used as components in various electronic devices because they have a small size, ensure high capacitance, and are easy to mount, and with the miniaturization and high output power of various electronic devices such as computers and mobile devices, the demand for miniaturization and high capacitance of multilayer ceramic capacitors is also increasing.
[0005] However, the ceramic body has a property of being broken without a plastic deformation zone when an external impact is applied, and in order to prevent the warping crack, a structure that can absorb or alleviate the tensile stress transmitted to the ceramic body is required.
[0006] Therefore, a method of suppressing the transfer of external warping stress to the ceramic body is used by applying a resin-based electrode added with resin to the external electrode structure, but in order to further improve the warping strength, various types of structural designs and modifications and materials are being studied. Summary of the invention
[0007] One aspect of the present disclosure provides a multilayer electronic component with improved warpage stress.
[0008] An aspect of the present disclosure suppresses occurrence of warping cracks in a multilayer electronic component by causing peeling in an external electrode when warping stress is applied from the outside.
[0009] However, aspects of the present disclosure are not limited to the above and may be more readily understood in the process of describing specific embodiments of the present disclosure.
[0010] According to one aspect of the present disclosure, a multilayer electronic component may include: a main body including a dielectric layer and internal electrodes alternately arranged with the dielectric layer in a first direction, the main body including a first surface and a second surface opposite to each other in the first direction, a third surface and a fourth surface opposite to each other and connected to the first surface and the second surface in the second direction, and a fifth surface and a sixth surface opposite to each other in a third direction and connected to the first surface to the fourth surface; and an external electrode including a connecting portion arranged on the third surface and the fourth surface and a band portion extending from the connecting portion to a portion of the first surface and the second surface, wherein the external electrode may include an electrode layer connected to the internal electrode and including a first conductive metal and glass, a conductive resin layer arranged on the electrode layer and including a second conductive metal and resin, and a silver (Ag) coating layer arranged in the band portion and between the electrode layer and the conductive resin layer, and the average thickness of the silver (Ag) coating layer may be greater than or equal to 2μm and less than or equal to 5μm.
[0011] According to one aspect of the present disclosure, a multilayer electronic component may include: a main body including a dielectric layer and internal electrodes alternately arranged with the dielectric layer in a first direction, the main body including a first surface and a second surface opposite to each other in the first direction, a third surface and a fourth surface opposite to each other and connected to the first surface and the second surface in the second direction, and a fifth surface and a sixth surface opposite to each other and connected to the first surface to the fourth surface in the third direction; and an external electrode including a connecting portion arranged on the third surface and the fourth surface and a band portion extending from the connecting portion to a portion of the first surface and the second surface, wherein the external electrode may include an electrode layer connected to the internal electrode and including a first conductive metal and glass, a conductive resin layer arranged on the electrode layer and including a second conductive metal and resin, and a silver (Ag) coating layer arranged in the band portion and between the electrode layer and the conductive resin layer, and the average atomic percentage of silver (Ag) in the silver (Ag) coating layer may be greater than or equal to 90at%.
[0012] One of the various effects of the present disclosure is to improve the warpage stress of a multilayer electronic component.
[0013] One of the various effects of the present disclosure is to suppress the occurrence of warping cracks in a multilayer electronic component by causing peeling in an external electrode when a warping stress is applied from the outside.
[0014] The advantages and effects of the present application are not limited to the foregoing and can be more easily understood in the process of describing a specific example embodiment of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] The above and other aspects, features and advantages of the present disclosure will be more clearly understood through the following detailed description in conjunction with the accompanying drawings, in which:
[0016] Figure 1 is a perspective view schematically illustrating a multilayer electronic component according to an example embodiment of the present disclosure;
[0017] Figure 2 An exploded perspective view schematically showing the stacking structure of the main body;
[0018] Figure 3 Schematically showing the Figure 1 A cross-sectional view taken along line II' in FIG.
[0019] Figure 4 Schematically showing the Figure 1 A cross-sectional view taken along line II-II';
[0020] Figure 5 Schematically shown Figure 3 A magnified view of the M region in FIG.
[0021] Figure 6 is an image captured by SEM of one region of an outer electrode according to an example embodiment of the present disclosure; and
[0022] 7A to 7D The EDS analysis included Figure 6 Elemental map of copper (Cu), silver (Ag), nickel (Ni), and tin (Sn) in an area of the material. DETAILED DESCRIPTION
[0023] Hereinafter, embodiments of the present disclosure will be described with reference to specific example embodiments and the accompanying drawings. However, embodiments of the present disclosure may be illustrated in many different forms and should not be construed as being limited to the specific embodiments set forth herein. The example embodiments disclosed herein are provided to better explain the present disclosure to those skilled in the art. In the accompanying drawings, the shapes and sizes of the elements may be exaggerated for clarity, and the same reference numerals will always be used to represent the same or similar elements.
[0024] In addition, in order to clearly describe the present disclosure in the drawings, the contents irrelevant to the description are omitted, and since the size and thickness of each component shown in the drawings are arbitrarily shown for the convenience of description, the present disclosure is not limited thereto. In addition, components having the same functions within the same conceptual scope are described using the same reference numerals. Throughout the specification, unless otherwise specified, when a specific part "includes" or "contains" a specific component, it indicates that other components are not excluded and other components may be further included.
[0025] In the drawings, a first direction may be defined as a thickness direction, a second direction may be defined as a length direction, and a third direction may be defined as a width direction.
[0026] Multilayer electronic components
[0027] Figure 1 is a perspective view schematically illustrating a multilayer electronic component according to an example embodiment of the present disclosure.
[0028] Figure 2 An exploded perspective view schematically showing the stacking structure of the main body.
[0029] Figure 3 Schematically showing the Figure 1 A cross-sectional view taken along line II' in FIG.
[0030] Figure 4 Schematically showing the Figure 1 A cross-sectional view taken along line II-II'.
[0031] Figure 5 Schematically shown Figure 3 Magnified view of the M region.
[0032] In the following, reference will be made to Figures 1 to 5 A multilayer electronic component according to an exemplary embodiment of the present disclosure is described in detail. However, as an example of a multilayer electronic component, a multilayer ceramic capacitor will be described, but the present disclosure is not limited thereto and the present disclosure may also be applied to various electronic products using a dielectric composition, such as an inductor, a piezoelectric element, a varistor, or a thermistor.
[0033] The multilayer electronic component 100 according to an example embodiment of the present disclosure may include a body 110 and external electrodes 131 and 132. The body 110 includes a dielectric layer 111 and internal electrodes 121 and 122 alternately disposed with the dielectric layer 111 in a first direction, and includes a first surface 1 and a second surface 2 opposite to each other in the first direction, a third surface 3 and a fourth surface 4 connected to the first surface 1 and the second surface 2 and opposite to each other in the second direction, and a fifth surface 5 and a sixth surface 6 connected to the first surface 1, the second surface 2, the third surface 3, and the fourth surface 4 and opposite to each other in the third direction. The external electrodes 131 and 132 include a connection portion disposed on the third surface 3 and the fourth surface 4 and a band portion extending from the connection portion to a portion of the first surface 1 and the second surface 2. The external electrodes 131 and 132 may include: electrode layers 131a and 132a, which are connected to the internal electrodes 121 and 122 and include a first conductive metal and glass; conductive resin layers 131c and 132c, which are disposed on the electrode layers 131a and 132a and include a second conductive metal and resin; and silver (Ag) coating layers 131b and 132b, which are disposed between the electrode layer and the conductive resin layer of the band portion, and the average thickness of the silver (Ag) coating layers 131b and 132b may be greater than or equal to 2μm and less than or equal to 5μm.
[0034] The body 110 may have dielectric layers 111 and internal electrodes 121 and 122 that are alternately stacked.
[0035] More specifically, the body 110 may include a capacitance forming part Ac that forms capacitance by including first and second internal electrodes 121 and 122 that are provided in the body 110 and alternately arranged to face each other with the dielectric layer 111 interposed therebetween.
[0036] The specific shape of the body 110 is not particularly limited, but as shown in the figure, the body 110 may have a hexahedral shape or a shape similar thereto. Due to the shrinkage of the ceramic powder particles included in the body 110 during the sintering process, the body 110 may not have a hexahedral shape with complete straight lines, but may have a substantially hexahedral shape.
[0037] The body 110 may have a first surface 1 and a second surface 2 opposite to each other in a first direction, a third surface 3 and a fourth surface 4 connected to the first surface 1 and the second surface 2 and opposite to each other in the second direction, and a fifth surface 5 and a sixth surface 6 connected to the first surface 1, the second surface 2, the third surface 3 and the fourth surface 4 and opposite to each other in a third direction.
[0038] In a state where a plurality of dielectric layers 111 forming the main body 110 are sintered, the dielectric layers 111 may be integrated to such an extent that it is difficult to identify the boundary between adjacent dielectric layers 111 without using a scanning electron microscope (SEM).
[0039] The raw material for forming the dielectric layer 111 is not limited as long as sufficient capacitance can be obtained. Generally, perovskite (ABO 3 )-based materials can be used. For example, barium titanate-based materials, lead composite perovskite-based materials, or strontium titanate-based materials can be used. The barium titanate-based materials may include BaTiO 3 -based ceramic particles. Examples of the ceramic particles include BaTiO 3 and (Ba 3 Ca 1-x )TiO x (0 < x < 1), Ba(Ti 3 Ca 1-y )O y (0 < y < 1), (Ba 3 Ca 1-x )(Ti x Zr 1-y )O y (0 < x < 1, 0 < y < 1), or Ba(Ti 3 Zr 1-y )O y (0 < y < 1) formed by partially solid-solubilizing calcium (Ca) and zirconium (Zr) in BaTiO 3 .
[0040] In addition, the raw material for forming the dielectric layer 111 can be obtained by adding various ceramic additives, organic solvents, adhesives, dispersants, etc. to particles such as barium titanate (BaTiO 3 ) according to the purpose of the present disclosure.
[0041] The thickness td of the dielectric layer 111 is not particularly limited.
[0042] However, in order to achieve a high capacitance of the multilayer electronic component, the thickness of the dielectric layer 111 may be less than or equal to 3.0 μm. And in order to more easily achieve miniaturization and high capacitance of the multilayer electronic component, the thickness of the dielectric layer 111 may be less than or equal to 1.0 μm, preferably less than or equal to 0.6 μm, and more preferably less than or equal to 0.4 μm.
[0043] Here, the thickness td of the dielectric layer 111 may refer to the thickness td of the dielectric layer 111 disposed between the first internal electrode 121 and the second internal electrode 122.
[0044] In addition, the thickness td of the dielectric layer 111 may refer to the size of the dielectric layer 111 in the first direction. In addition, the thickness td of the dielectric layer 111 may refer to the average thickness td of the dielectric layer 111 and may refer to the average size of the dielectric layer 111 in the first direction.
[0045] The average thickness of the dielectric layer 111 can be measured by scanning an image of a cross section of the body 110 in the first direction and the second direction with a scanning electron microscope (SEM) at a magnification of 10,000 times. More specifically, the average size of one dielectric layer 111 in the first direction may refer to an average value calculated by measuring the first direction size of 30 points spaced apart from each other at equal intervals in the second direction of one dielectric layer 111 in the scanned image. The 30 points spaced apart from each other at equal intervals may be specified in the capacitor forming portion Ac described below. In addition, when the average value is measured by extending the average value measurement to 10 dielectric layers 111, the average size of the dielectric layer 111 in the first direction may be further generalized.
[0046] The internal electrodes 121 and 122 may be alternately stacked with the dielectric layers 111 .
[0047] The internal electrodes 121 and 122 may include a first internal electrode 121 and a second internal electrode 122, and the first internal electrode 121 and the second internal electrode 122 may be alternately arranged to face each other with the dielectric layer 111 interposed therebetween, and may be exposed to the third surface 3 and the fourth surface 4 of the body, respectively. Here, “exposed to one surface of the body” may mean in contact with one surface of the body.
[0048] More specifically, the first inner electrode 121 may be spaced apart from the fourth surface 4 and may be exposed through the third surface 3, and the second inner electrode 122 may be spaced apart from the third surface 3 and may be exposed through the fourth surface 4. The first outer electrode 131 may be disposed on the third surface 3 of the body 110 and connected to the first inner electrode 121, and the second outer electrode 132 may be disposed on the fourth surface 4 of the body 110 and connected to the second inner electrode 122.
[0049] That is, the first internal electrode 121 may be connected to the first external electrode 131 without being connected to the second external electrode 132, and the second internal electrode 122 may be connected to the second external electrode 132 without being connected to the first external electrode 131. In this case, the first internal electrode 121 and the second internal electrode 122 may be electrically isolated from each other by the dielectric layer 111 disposed therebetween.
[0050] In addition, the body 110 may be formed by alternately stacking ceramic green sheets having the first internal electrodes 121 formed thereon and ceramic green sheets having the second internal electrodes 122 formed thereon and then sintering the ceramic green sheets.
[0051] The material forming the internal electrodes 121 and 122 is not particularly limited, and any material having excellent conductivity may be used. For example, the internal electrodes 121 and 122 may include one or more of nickel (Ni), copper (Cu), palladium (Pd), silver (Ag), gold (Au), platinum (Pt), tin (Sn), tungsten (W), titanium (Ti), and alloys thereof.
[0052] In addition, the internal electrodes 121 and 122 may be formed by printing a conductive paste for internal electrodes including one or more of nickel (Ni), copper (Cu), palladium (Pd), silver (Ag), gold (Au), platinum (Pt), tin (Sn), tungsten (W), titanium (Ti), and alloys thereof on a ceramic green sheet. The printing method of the conductive paste for internal electrodes may be a screen printing method or a gravure printing method, but the present disclosure is not limited thereto.
[0053] In addition, the thickness te of the internal electrodes 121 and 122 is not particularly limited.
[0054] However, in order to achieve high capacitance of the multilayer electronic components, the thickness of the internal electrodes 121 and 122 may be less than or equal to 1.5 μm, or may be less than or equal to 1.0 μm, and in order to more easily achieve miniaturization and high capacitance of the multilayer electronic components, the thickness of the internal electrodes 121 and 122 may be less than or equal to 0.6 μm, and more preferably may be less than or equal to 0.4 μm.
[0055] Here, the thickness te of the internal electrodes 121 and 122 may refer to the size of the internal electrodes 121 and 122 in the first direction. In addition, the thickness te of the internal electrodes 121 and 122 may refer to the average thickness te of the internal electrodes 121 and 122 and may refer to the average size of the internal electrodes 121 and 122 in the first direction.
[0056] The average size of the internal electrodes 121 and 122 in the first direction may be measured by scanning an image of a cross section of the body 110 in the first direction and the second direction with a scanning electron microscope (SEM) at a magnification of 10,000 times. More specifically, the average size of one internal electrode in the first direction may refer to an average value calculated by measuring the first direction size of one internal electrode at 30 points spaced apart from each other at equal intervals in the second direction in the scanned image. 30 points spaced apart from each other at equal intervals may be specified in the capacitance forming portion Ac. In addition, when the average value is measured by extending the average value measurement to 10 internal electrodes, the average size of the internal electrode in the first direction may be further generalized.
[0057] In addition, in the example embodiment of the present disclosure, an average thickness td of at least one of the plurality of dielectric layers 111 and an average thickness te of at least one of the plurality of internal electrodes 121 and 122 may satisfy 2×te <td。
[0058] In other words, the average thickness td of one dielectric layer 111 may be greater than twice the average thickness te of one internal electrode 121 or 122. Preferably, the average thickness td of the plurality of dielectric layers 111 may be greater than twice the average thickness te of the plurality of internal electrodes 121 and 122.
[0059] Generally, for high voltage electronic components, reliability is a major issue due to the decrease in breakdown voltage (BDV) under a high voltage environment.
[0060] Therefore, in order to prevent the breakdown voltage (BDV) from decreasing under a high voltage environment, the average thickness td of the dielectric layer 111 can be made greater than twice the average thickness te of the internal electrodes 121 and 122, thereby increasing the thickness of the dielectric layer (which is the distance between the internal electrodes) and improving the breakdown voltage characteristics.
[0061] When the average thickness td of the dielectric layer 111 is less than twice the average thickness te of the internal electrodes 121 and 122 , the average thickness of the dielectric layer as a distance between the internal electrodes may be thin, which may reduce a breakdown voltage and cause a short circuit between the internal electrodes.
[0062] In the high voltage electronic component, an average thickness te of the internal electrodes may be less than or equal to 1 μm, and an average thickness td of the dielectric layer may be less than or equal to 3.0 μm, but the present disclosure is not necessarily limited thereto.
[0063] In addition, the body 110 may include cover parts 112 and 113 provided on both end surfaces of the capacitance forming part Ac in the first direction.
[0064] More specifically, the body 110 may include an upper cover portion 112 disposed above the capacitance forming portion Ac in the first direction, and a lower cover portion 113 disposed below the capacitance forming portion Ac in the first direction.
[0065] The upper cover portion 112 and the lower cover portion 113 may be formed by stacking a single dielectric layer 111 or two or more dielectric layers 111 on the upper surface and the lower surface of the capacitor forming portion Ac in the first direction, respectively, and may generally be used to prevent damage to the internal electrodes 121 and 122 due to physical stress or chemical stress.
[0066] The upper cover portion 112 and the lower cover portion 113 do not include the internal electrodes 121 and 122, and may include the same material as the dielectric layer 111. That is, the upper cover portion 112 and the lower cover portion 113 may include a ceramic material, for example, barium titanate (BaTiO 3 ) based ceramic materials.
[0067] In addition, the thickness tc of the cover parts 112 and 113 is not particularly limited.
[0068] However, to more easily achieve miniaturization and high capacitance of multilayer electronic components, the thickness tc of the caps 112 and 113 may be 100 μm or less, preferably 30 μm or less, and more preferably 20 μm or less in ultra-small products.
[0069] Here, the thickness tc of the cover parts 112 and 113 may refer to the size of the cover parts 112 and 113 in the first direction. In addition, the thickness tc of the cover parts 112 and 113 may refer to the average thickness tc of the cover parts 112 and 113 and may refer to the average size of the cover parts 112 and 113 in the first direction.
[0070] The average size of the cover portions 112 and 113 in the first direction may be measured by scanning an image of a cross section of the body 110 in the first direction and the second direction using a scanning electron microscope (SEM) at a magnification of 10,000 times. More specifically, the average size of the cover portions 112 and 113 in the first direction may refer to an average value calculated by measuring the size of one cover portion in the first direction at 30 points spaced apart from each other at equal intervals in the second direction in the scanned image.
[0071] In addition, the average size of the cover portion in the first direction measured by the above method may be substantially the same as the average size of the cover portion in the first direction in the cross-section of the body 110 in the first and third directions.
[0072] In addition, the multilayer electronic component 100 may include side edge parts 114 and 115 provided on both end surfaces of the body 110 in the third direction.
[0073] More specifically, the side edge portions 114 and 115 may include a first side edge portion 114 disposed on the fifth surface 5 of the body 110 , and a second side edge portion 115 disposed on the sixth surface 6 of the body 110 .
[0074] As shown, the side margin parts 114 and 115 may refer to regions between both end surfaces of the first and second internal electrodes 121 and 122 in the third direction and a boundary surface of the body 110 based on the cross-section of the body 110 in the first and third directions.
[0075] The side edge portions 114 and 115 may be formed by not coating the conductive paste on the ceramic green sheet forming the capacitor forming portion Ac except for the region where the internal electrodes 121 and 122 are to be formed, and in order to suppress the step portion caused by the internal electrodes 121 and 122, after cutting the stacked internal electrodes 121 and 122 to expose the side surface of the capacitor forming portion Ac in the third direction, a single dielectric layer 111 or two or more dielectric layers 111 may be stacked and formed on both side surfaces of the capacitor forming portion Ac in the third direction.
[0076] The side margin portions 114 and 115 may generally serve to prevent damage to the internal electrodes 121 and 122 due to physical stress or chemical stress.
[0077] The first side margin portion 114 and the second side margin portion 115 do not include the internal electrodes 121 and 122, and may include the same material as the dielectric layer 111. That is, the first side margin portion 114 and the second side margin portion 115 may include a ceramic material, for example, barium titanate (BaTiO 3 ) based ceramic materials.
[0078] In addition, the widths (wm) of the first side margin portion 114 and the second side margin portion 115 are not particularly limited.
[0079] However, in order to more easily achieve miniaturization and high capacitance of the multilayer electronic component 100, the width (wm) of the side edge portions 114 and 115 may be less than or equal to 100 μm, preferably less than or equal to 30 μm, and more preferably less than or equal to 20 μm in ultra-small products.
[0080] Here, the width (wm) of the side edge portions 114 and 115 may refer to the size of the side edge portions 114 and 115 in the third direction. In addition, the width (wm) of the side edge portions 114 and 115 may refer to the average width (wm) of the side edge portions 114 and 115, and may refer to the average size of the side edge portions 114 and 115 in the third direction.
[0081] The average size of the side edge portions 114 and 115 in the third direction may be measured by scanning an image of a cross section of the body 110 in the first direction and the third direction using a scanning electron microscope (SEM) at a magnification of 10,000 times. More specifically, the average size of the side edge portions 114 and 115 in the third direction may refer to an average value calculated by measuring the size of one side edge portion in the third direction at 10 points spaced apart from each other at equal intervals in the first direction in the scanned image.
[0082] In the exemplary embodiment of the present disclosure, a structure in which the multilayer electronic component 100 has two external electrodes 131 and 132 is described, but the number or shape of the external electrodes 131 and 132 may be changed according to the shapes of the internal electrodes 121 and 122 or other purposes.
[0083] The external electrodes 131 and 132 may be disposed on the body 110 , and may be connected to the internal electrodes 121 and 122 .
[0084] More specifically, the external electrodes 131 and 132 may include a first external electrode 131 and a second external electrode 132 respectively disposed on the third surface 3 and the fourth surface 4 of the body 110 and respectively connected to the first internal electrode 121 and the second internal electrode 122. That is, the first external electrode 131 may be disposed on the third surface 3 of the body and connected to the first internal electrode 121, and the second external electrode 132 may be disposed on the fourth surface 4 of the body and connected to the second internal electrode 122.
[0085] In addition, the external electrodes 131 and 132 may be disposed to extend on a portion of the first surface 1 and the second surface 2 of the body 110, or may be disposed to extend on a portion of the fifth surface 5 and the sixth surface 6 of the body 110. That is, the first external electrode 131 may be disposed on a portion of the first surface 1, the second surface 2, the fifth surface 5, and the sixth surface 6 of the body 110 and disposed on the third surface 3 of the body 110, and similarly, the second external electrode 132 may be disposed on a portion of the first surface 1, the second surface 2, the fifth surface 5, and the sixth surface 6 of the body 110 and disposed on the third surface 3 of the body 110.
[0086] Specifically, the external electrodes 131 and 132 may include a connection portion disposed on the third surface 3 and the fourth surface 4 , and a band portion extending from the connection portion to a portion of the first surface 1 and the second surface 2 .
[0087] The first external electrode 131 may include a first connection portion disposed on the third surface 3, a first band portion extending from the first connection portion to a portion of the first surface 1, and a third band portion extending from the first connection portion to a portion of the second surface 2. The second external electrode 132 may include a second connection portion disposed on the fourth surface 4, a second band portion extending from the second connection portion to a portion of the first surface 1, and a fourth band portion extending from the second connection portion to a portion of the second surface 2.
[0088] Reference Figure 3 In the present disclosure, a “connecting portion” may refer to a portion of an external electrode disposed between an extension line EL1 on the first surface and an extension line EL2 on the second surface, and a “band portion” may refer to a portion of an external electrode disposed below the extension line EL1 on the first surface in a first direction and a portion of an external electrode disposed above the extension line EL2 on the second surface in the first direction.
[0089] In addition, the external electrodes 131 and 132 may be formed using any material as long as they have conductivity, such as metal, and their specific materials may be determined in consideration of electrical characteristics, structural stability, etc., and may also have a multi-layered structure.
[0090] For example, the external electrodes 131 and 132 may include electrode layers 131a and 132a disposed in contact with the body 110 and conductive resin layers 131c and 132c disposed on the electrode layers 131a and 132a. For example, the electrode layers 131a and 132a and the conductive resin layers 131c and 132c may be formed by transferring a sheet including a conductive metal onto the body or by coating / dipping a paste.
[0091] More specifically, the electrode layers 131 a and 132 a may be sintered electrodes including a first conductive metal and glass, and the conductive resin layers 131 c and 132 c may be resin-based electrodes including a second conductive metal and resin.
[0092] That is, the conductive metal included in the first electrode layers 131 a and 132 a may be referred to as a first conductive metal, and the conductive metal included in the conductive resin layers 131 c and 132 c may be referred to as a second conductive metal.
[0093] The conductive metal may include one or more selected from the group consisting of nickel (Ni), copper (Cu), palladium (Pd), silver (Ag), gold (Au), platinum (Pt), tin (Sn), tungsten (W), titanium (Ti) and alloys thereof, but the present disclosure is not particularly limited thereto. That is, there may be one or more types of conductive metals.
[0094] More specifically, the electrode layers 131 a and 132 a serve to improve adhesion with the body 110 by including glass, and the conductive resin layers 131 c and 132 c serve to improve warping strength by including resin.
[0095] The first conductive metal used in the electrode layers 131a and 132a is not particularly limited as long as any material that can be electrically connected to the internal electrodes 121 and 122 to form an electrostatic capacity can be used, and the first conductive metal may include, for example, one or more selected from the group consisting of nickel (Ni), copper (Cu), palladium (Pd), silver (Ag), gold (Au), platinum (Pt), tin (Sn), tungsten (W), titanium (Ti), and alloys thereof. The first electrode layers 131a and 132a may be formed by coating a conductive paste prepared by adding glass frit to conductive metal particles and then sintering the conductive paste.
[0096] The second conductive metal included in the conductive resin layers 131 c and 132 c may serve to electrically connect the electrode layers 131 a and 132 a .
[0097] The second conductive metal included in the conductive resin layers 131c and 132c is not particularly limited as long as it is any material that can be electrically connected to the electrode layers 131a and 132a, and the second conductive metal may include one or more selected from the group consisting of nickel (Ni), copper (Cu), palladium (Pd), silver (Ag), gold (Au), platinum (Pt), tin (Sn), tungsten (W), titanium (Ti) and alloys thereof.
[0098] In this case, the first conductive metal and the second conductive metal may be the same, and for example, the first conductive metal and the second conductive metal may be copper (Cu). However, the present disclosure is not particularly limited thereto, and the first conductive metal and the second conductive metal may be different from each other. In addition, when the first conductive metal and the second conductive metal are multiple, the same metal or different metals may be included between the first conductive metal and the second conductive metal.
[0099] The second conductive metal included in the conductive resin layers 131c and 132c may include one or both of flaky particles and spherical particles. That is, the conductive metal may be formed only of flaky particles, or only of spherical particles, or may be a mixture of flaky particles and spherical particles. Here, the spherical particles may also include a shape that is not completely spherical, and, for example, may include a form in which the length ratio of the major axis to the minor axis (major axis / minor axis) is less than or equal to 1.45. The flaky particles may refer to particles having a flat and elongated shape, and are not particularly limited thereto, but, for example, the length ratio of the major axis to the minor axis (major axis / minor axis) may be greater than or equal to 1.95.
[0100] The lengths of the major and minor axes of the spherical particles and the plate-like particles can be measured from an image obtained by scanning a cross section in the first and second directions taken at the center in the third direction of the multilayer electronic component with a scanning electron microscope (SEM).
[0101] The resin included in the conductive resin layers 131c and 132c can ensure adhesion properties and act as a shock absorber. The resin included in the conductive resin layers 131c and 132c is not particularly limited as long as the resin can have adhesion properties and shock absorbing properties and can be mixed with conductive metal particles to make a paste, and the resin can include, for example, an epoxy resin.
[0102] In addition, the conductive resin layers 131c and 132c may include a plurality of metal particles, an intermetallic compound, and a resin. By including the intermetallic compound, the electrical connectivity with the electrode layers 131a and 132a may be further improved. The intermetallic compound may be used to improve the electrical connectivity by connecting a plurality of metal particles, and may be used to surround and connect a plurality of metal particles to each other.
[0103] In this case, the intermetallic compound may include a metal having a melting point lower than the solidification temperature of the resin. That is, because the intermetallic compound includes a metal having a melting point lower than the solidification temperature of the resin, the metal having a melting point lower than the solidification temperature of the resin melts during the drying and solidification process and forms an intermetallic compound with some metal particles to surround the metal particles. In this case, the intermetallic compound may preferably include a metal having a low melting point of 300° C. or less.
[0104] For example, the intermetallic compound may include Sn having a melting point of 213° C. to 220° C. Sn melts during the drying and solidification process, and the molten Sn wets high melting point metal particles such as Ag, Ni, or Cu by capillary action and reacts with some of the Ag, Ni, or Cu metal particles to form an intermetallic compound such as Ag. 3 Sn、Ni 3 Sn 4 , Cu 6 Sn 5 and Cu 3 Sn. Ag, Ni or Cu that does not participate in the reaction remains in the form of metal particles.
[0105] Thus, the plurality of metal particles may include one or more of Ag, Ni, and Cu, and the intermetallic compound may include Ag. 3 Sn、Ni 3 Sn 4 , Cu 6 Sn 5 and Cu 3 One or more of Sn.
[0106] The present disclosure may prevent the occurrence of a warping crack by causing peeling in an external electrode structure by applying a silver (Ag) coating structure to a band portion of an external electrode to which a warping stress is intensively applied.
[0107] The external electrodes 131 and 132 according to an example embodiment of the present disclosure may include silver (Ag) coating layers 131 b and 132 b disposed between electrode layers 131 a and 132 a of the strip portion and conductive resin layers 131 c and 132 c .
[0108] In other words, the silver (Ag) coating layers 131b and 132b may be disposed in the band region of the outer electrode. Figure 3, silver (Ag) coatings 131b and 132b may be provided in portions below the extension line EL1 of the first surface in the first direction and above the extension line EL2 of the second surface in the first direction. More specifically, the silver (Ag) coatings 131b and 132b may be provided between the electrode layers 131a and 132a of the band portion and the conductive resin layers 131c and 132c, and the silver (Ag) coatings 131b and 132b may be provided in portions below the extension line EL1 of the first surface in the first direction and above the extension line EL2 of the second surface in the first direction.
[0109] Silver (Ag) coatings 131b and 132b may be provided between the electrode layers 131a and 132a of the band portion and the conductive resin layers 131c and 132c so that when warping stress is applied, the occurrence of warping cracks may be further suppressed by causing peeling between the electrode layers 131a and 132a and the conductive resin layers 131c and 132c.
[0110] In this case, the average thickness of the silver (Ag) coating layers 131 b and 132 b may be greater than or equal to 2 μm and less than or equal to 5 μm.
[0111] When the average thickness of the silver (Ag) coating layers 131 b and 132 b satisfies 2 μm or more and 5 μm or less, peeling due to warping stress may be more easily caused.
[0112] When the average thickness of the silver (Ag) coatings 131b and 132b is less than 2 μm, peeling may be partially caused, but there may be a risk of warping cracks, and when the average thickness of the silver (Ag) coatings 131b and 132b is greater than 5 μm, there may be a risk that the adhesion between the electrode layers 131a and 132a and the conductive resin layers 131c and 132c may be reduced, thereby weakening the adhesion strength.
[0113] The method of measuring the average thickness of the silver (Ag) coatings 131b and 132b can be obtained, for example, by measuring the thickness of the silver (Ag) coatings 131b and 132b at various points based on the cross section of the multilayer electronic component 100 in the first direction and the second direction observed under SEM. More specifically, after measuring the size (thickness) of the straight line in the direction perpendicular to the electrode layers 131a and 132a at 10 points spaced apart from each other at equal intervals, the value obtained by averaging the size thereof can be referred to as the average thickness of the silver (Ag) coatings 131b and 132b. Alternatively, the average thickness may refer to a value obtained by measuring and averaging the size of the first direction at 10 points spaced apart from each other at equal intervals in the region of the first surface 1 and the second surface 2 of the silver (Ag) coatings 131b and 132b that are substantially parallel to the body, but the present disclosure is not particularly limited thereto. Even if not described in the present disclosure, other methods and / or tools understood by a person of ordinary skill in the art may also be used.
[0114] The silver (Ag) coating layers 131 b and 132 b according to an example embodiment of the present disclosure may not be disposed between the electrode layers 131 a and 132 a of the connection part and the conductive resin layers 131 c and 132 c .
[0115] When the silver (Ag) coatings 131b and 132b are provided on the connection portions, peeling may be more easily caused, but the adhesion between the electrode layers 131a and 132a and the conductive resin layers 131c and 132c may be reduced, and therefore, there is a risk that complete delamination may occur between the electrode layers 131a and 132a and the conductive resin layers 131c and 132c.
[0116] In addition, the average atomic percentage of silver (Ag) in the silver (Ag) coating layers 131b and 132b may be greater than or equal to 90at%, and preferably may be greater than or equal to 95at%. When expressed as an average weight percentage (wt%), the average weight percentage of silver (Ag) may be greater than or equal to 95wt%, preferably may be greater than or equal to 97wt%, and more preferably may be greater than or equal to 98wt%, and at various points, there may be a plurality of points where the average weight percentage (wt%) is greater than 99wt%.
[0117] The method of measuring the average atomic percentage (or average weight percentage) of silver (Ag) is not particularly limited, but based on the cross-section of the multilayer electronic component 100 in the first direction and the second direction, when energy dispersive X-ray spectroscopy (EDS) analysis is performed at 10 points in the center of the silver (Ag) coating layers 131b and 132b, its average atomic percentage (or average weight percentage) may be the average value of the atomic percentage values (or weight percentage values) of silver (Ag) measured at the 10 points. Alternatively, its average atomic percentage (or average weight percentage) may refer to the value of the atomic percentage (or weight percentage) of silver (Ag) measured when EDS analysis of silver (Ag) is performed on the entire area of the silver (Ag) coating layers 131b and 132b. Even if not described in the present disclosure, other methods and / or tools understood by those of ordinary skill in the art may be used.
[0118] In other words, the silver (Ag) coating layers 131 b and 132 b correspond to pure silver (Ag) including little or no other conductive metal or alloy, or may be considered to be substantially pure silver (Ag).
[0119] The method of forming the silver (Ag) coating layer is not particularly limited, but can be formed by, for example, a galvanic displacement reaction.
[0120] More specifically, after the sintering of the electrode layers 131a and 132a is completed, the electrode layers 131a and 132a are immersed in a silver (Ag) aqueous solution, for example, 10 mM to 1 M (molar concentration, 1 M = 1 mol / L) of silver nitrate (AgNO 3 ) for 10 to 60 minutes to allow silver (Ag) to undergo a reduction reaction, and then the immersed electrode layers 131a and 132a are washed two to three times with distilled water, thereby removing excessively formed silver (Ag) reduction products or silver (Ag) ions to form a silver (Ag) coating layer having a substantially constant thickness.
[0121] When immersed in silver nitrate (AgNO 3 ) aqueous solution, a silver (Ag) coating layer may be formed by immersing only the band portion of the electrode layer. Alternatively, after immersing all portions of the electrode layer to form the silver (Ag) coating layer, the silver (Ag) coating layer formed at the connecting portion may be removed to form the (Ag) coating layer only on the electrode layer of the band portion, but the present disclosure is not particularly limited thereto.
[0122] Then, a paste including a conductive metal and a resin may be coated or transferred onto the electrode layers 131a and 132a and the silver (Ag) coating layers 131b and 132b to form conductive resin layers 131c and 132c.
[0123] In addition, the length of the region where the silver (Ag) coating layer according to the example embodiment of the present disclosure is formed may be 50% or more of the length of the electrode layer of the strip portion.
[0124] There is no particular limitation on the upper limit of the length of the silver (Ag) coating for inducing peeling. However, for the adhesion strength between the electrode layers 131a and 132a and the conductive resin layers 131c and 132c, the upper limit of the length of the silver (Ag) coating can be less than or equal to 80%, and preferably less than or equal to 70%.
[0125] In other words, the length of the region where the silver (Ag) coating is formed can be greater than 50% of the length of the boundary region between the electrode layer and the conductive resin layer of the tape portion. More specifically, when the length of the electrode layers 131a and 132a of the tape portion is defined as IFL and the length of the silver (Ag) coatings 131b and 132b is defined as L, 50% ≤ L / IFL can be satisfied, and L / IFL ≤ 80% can be satisfied.
[0126] For example, referring to Figure 5 , here, the length IFL of the electrode layers 131a and 132a of the tape portion can refer to the sum L + L' of the length L of the interface between the electrode layers 131a and 132a of the tape portion and the silver (Ag) coatings 131b and 132b and the length (L', not shown) of the interface between the electrode layers 131a and 132a of the tape portion and the conductive resin layers 131c and 132c. The length L of the silver (Ag) coatings 131b and 132b can refer to the length L of the interface between the electrode layers 131a and 132a of the tape portion and the silver (Ag) coatings 131b and 132b.
[0127] The ratio L / IFL of the length L of the silver (Ag) coatings 131b and 132b of the tape portion to the length IFL of the electrode layers 131a and 132a of the tape portion can satisfy 50% ≤ L / IFL, and L / IFL ≤ 80%, such that peeling due to warpage stress can be more easily induced. On the other hand, when comparing the L / IFL values of 70% and 80%, the peeling effect due to warpage stress may show little difference.
[0128] When the ratio L / IFL of the length L of the silver (Ag) coatings 131b and 132b of the tape portion to the length IFL of the electrode layers 131a and 132a of the tape portion is less than 50% (L / IFL < 50%), peeling may occur partially, but there is a risk of warpage cracks appearing. And when the ratio L / IFL of the length L of the silver (Ag) coatings 131b and 132b of the tape portion to the length IFL of the electrode layers 131a and 132a of the tape portion is greater than 80% (80% < L / IFL), there may be a risk that the adhesion between the electrode layers 131a and 132a and the conductive resin layers 131c and 132c may decrease, thereby weakening the adhesion strength. The silver (Ag) coating can include a plurality of silver islands spaced apart from each other.
[0129] The method of measuring the length IFL of the electrode layer of the band portion and the length L of the silver (Ag) coating of the band portion is not particularly limited. For example, based on the cross-section of the multilayer electronic component in the first direction and the second direction, after taking an image of the area of the band portion of the external electrode in which the silver (Ag) coating is provided using a scanning electron microscope (SEM) at a magnification of 2000 times, the length IFL of the electrode layer can be measured using the freehand line function of the Image J program. More specifically, the length L (section to be measured) of the interface between the electrode layer of the band portion and the silver (Ag) coating of the band portion can be measured by selecting the freehand line function, the length of the interface between the electrode layer of the band portion and the conductive resin layer of the band portion can be measured, and the length IFL of the electrode layer of the band portion (which is the sum of L and L') can be obtained.
[0130] As an example of a more specific method of measuring the content of the elements contained in the silver (Ag) coating layers 131b and 132b, in the case of a destructive method, a scanning electron microscope-energy dispersive X-ray spectrometer (SEM-EDS), a transmission electron microscope-energy dispersive X-ray spectrometer (TEM-EDS), or a scanning transmission electron microscope-energy dispersive X-ray spectrometer (STEM-EDS) can be used to analyze the components in the dielectric grains at the center of the sheet. First, an analysis sample of the thin sheet is prepared using a focused ion beam (FIB) device in an area containing a dielectric microstructure in a cross section of a sintered body. Then, an argon (Ar) ion milling is used to remove the damaged layer on the surface of the analysis sample of the thin sheet, and then, a qualitative / quantitative analysis is performed by mapping each component in an image obtained using SEM-EDS, TEM-EDS, or STEM-EDS. In this case, the qualitative / quantitative analysis graph of each component can be expressed in terms of weight percentage (wt%), atomic percentage (at%), or molar percentage (mol%) of each element.
[0131] In another method, the sheet is pulverized to select a region including a dielectric microstructure, and in the portion including the selected dielectric microstructure, a device such as an inductively coupled plasma spectrometer (ICP-OES) and an inductively coupled plasma mass spectrometer (ICP-MS) may be used to analyze the composition of the region including the dielectric microstructure. Even if not described in the present disclosure, other methods and / or tools understood by a person of ordinary skill in the art may be used.
[0132] The plating layers 131d, 132d, 131e, and 132e may be used to improve mounting characteristics.
[0133] The type of plating 131d, 132d, 131e and 132e is not particularly limited, and may be a single plating 131d or 132d including one or more of nickel (Ni), tin (Sn), palladium (Pd) and their alloys, or may be a plurality of plating layers 131d, 132d, 131e and 132e.
[0134] For a more specific example of the plating layers 131d, 132d, 131e, and 132e, the plating layers 131d, 132d, 131e, and 132e may be Ni plating layers or Sn plating layers, and may be in a form in which Ni plating layers and Sn plating layers are sequentially formed on the conductive resin layers 131c and 132c, and may be in a form in which Sn plating layers, Ni plating layers, and Sn plating layers are sequentially formed. In addition, the plating layers 131d, 132d, 131e, and 132e may include a plurality of Ni plating layers and / or a plurality of Sn plating layers.
[0135] The size of the multilayer electronic component 100 is not particularly limited.
[0136] However, in order to achieve both miniaturization and high capacitance, it is necessary to thin the thickness of the dielectric layer and the internal electrode to increase the number of stacks, and in order to improve the dielectric breakdown voltage (BDV) characteristics under high voltage, it is necessary to ensure that the thickness of the dielectric layer and the internal electrode is constant, and considering all characteristics such as mechanical strength according to warping stress, the effect according to the present disclosure is more significant for a multilayer electronic component 100 having a size of 3216 (length × width: 3.2 mm × 1.6 mm) or smaller.
[0137] Hereinafter, the present disclosure will be described in more detail through examples, but these are intended to help specific understanding of the present invention, and the scope of the present disclosure is not limited to the examples.
[0138] (Example)
[0139] Examples 1 to 10 were manufactured as follows. After a copper (Cu) paste was coated on a ceramic body and sintered to form an electrode layer, the electrode layer was immersed in 0.1 mM to 0.1 M silver nitrate (AgNO 3 ) aqueous solution for 10 to 60 minutes to cause a silver (Ag) reduction reaction, and then the immersed electrode layer is washed with distilled water to remove excess silver (Ag) reduction products falling off its surface, thereby forming a silver (Ag) coating on the electrode layer. Then, the silver (Ag) coating formed on the surface of the third surface and the fourth surface of the ceramic body of the electrode layer is mounted on a carrier plate and removed using an adhesive tape. Then, a copper (Cu)-epoxy paste is applied to the electrode layer and the silver (Ag) coating and sintered to form a conductive resin layer. Then, a nickel (Ni) plating layer and a tin (Sn) plating layer are formed on the conductive resin layer to complete the sheet. According to the silver nitrate (AgNO 3) aqueous solution and the immersion time to form silver (Ag) coatings with various thicknesses and lengths.
[0140] In Example 1, in addition to immersing the electrode layer in 0.1 M silver nitrate (AgNO 3 ) aqueous solution for 30 minutes to cause a silver (Ag) reduction reaction, and then washing the immersed electrode layer with distilled water to remove excess silver (Ag) reduction products falling off its surface, thereby forming a silver (Ag) coating on the electrode layer. In this case, the average thickness of the silver (Ag) coating in the band portion was 3.4 μm, and the ratio of the length L of the silver (Ag) coating in the band portion to the length IFL of the electrode layer was about 82%.
[0141] When referring to the images of the scanning electron microscope (SEM) and EDS analysis as Example 1 of the present disclosure Figure 6 and 7A to 7D When describing, for the warpage strength test, 10N / mm 2 A warping stress of 1000° was applied to the sheet to perform a severe limit evaluation higher than the guaranteed level, and then, when the region between the electrode layer and the conductive resin layer of the belt portion was observed at a magnification of 2000 times with a scanning electron microscope (SEM), it was confirmed that peeling occurred. Figure 6 When SEM-EDS analysis was performed on the dotted line area (area of the belt portion) in FIG. 1 , when observing the area in which copper (Cu), silver (Ag), nickel (Ni) and tin (Sn) were detected, it was confirmed that the silver (Ag) coating between the electrode layer along the belt portion and the conductive resin layer of the belt portion was peeled off.
[0142] Next, Table 1 reflects evaluations of warpage cracking, peeling, and adhesion strength according to the average thickness of the silver (Ag) coating layer of each example.
[0143] Example 2 is an example in which an electrode layer is formed on a ceramic body, a conductive resin layer is formed on the electrode layer, and a silver (Ag) coating layer is not formed. A sheet is manufactured by the same process as Example 1 except for the process of forming the silver (Ag) coating layer.
[0144] In Examples 3 to 5, except for changing the amount of silver nitrate (AgNO 3 ) were made differently to produce the average thickness of the silver (Ag) coating layer, sheets were manufactured in the same manner as in Example 1. More specifically, the average thickness of the silver (Ag) coating layer in each sheet of Example 3 was less than 2 μm, the average thickness of the silver (Ag) coating layer in each sheet of Example 4 was greater than or equal to 2 μm and less than or equal to 5 μm, and the average thickness of the silver (Ag) coating layer in each sheet of Example 5 was greater than 5 μm.
[0145] In the warpage strength evaluation, after manufacturing 20 sheets for each example, the 20 sheets were mounted on a warpage strength (piezoelectric method) substrate (1.6T according to the AEC-Q200 evaluation rules) for a limit evaluation exceeding the guaranteed range, and then, all 20 sheets were removed from the board, and the cross-sections of each sheet in the first and second directions were confirmed to count and reflect the number of sheets in which warpage cracks and peeling occurred.
[0146] Here, the evaluation method of the warpage strength (piezoelectric method) can be described as follows. First, five sample sheets are mounted on a piezoelectric PCB, and in order to express the piezoelectric characteristics, a DC bias is applied to the sheet to generate a potential difference, and then bending is applied. A potential difference occurs due to the external force caused by bending, and a microcurrent generated due to the change in the potential difference can be measured and expressed in a graph, and the graph expressed in this case is called a piezoelectric graph, which is a method of evaluating whether defects occur and points occur by interpreting the piezoelectric graph.
[0147] In the adhesion strength evaluation, when 18N / mm is applied according to the AEC-Q200 standard 2 When stress was applied to the end surface of the sheet in the first direction and the second direction for 60 seconds, if a capacitance change of more than 10% or sheet detachment occurred, it was determined to be defective, and the number of defective sheets was counted and reflected in Table 1.
[0148] After evaluating the warpage strength and the adhesion strength, during the evaluation of the adhesion strength, if even one sheet had a defect, it was determined as ×, and even if there was no sheet with a defect in the adhesion strength, when any sheet among the 20 sheets had a warpage crack, or all 20 sheets were not completely peeled off, it was determined as a triangle (△), and among all 20 sheets, when peeling occurred without an adhesion strength defect or a warpage crack, it was determined as a circle (○).
[0149] Table 1:
[0150] Example Warping crack Stripping Adhesion strength Sure Example 2 5 / 20 5 / 20 0 / 20 △ Example 3 3 / 20 10 / 20 0 / 20 △ Example 4 0 / 20 20 / 20 0 / 20 O Example 5 0 / 20 20 / 20 2 / 20 X
[0151] In Example 2, since the silver (Ag) coating layer was not formed, warping cracks occurred in 5 of the 20 sheets due to the warping stress, and peeling occurred in 5 sheets, and there was no sheet with adhesion strength defect. In Example 2, which is the same case as the conventional sheet in which the silver (Ag) coating layer was not formed, the adhesion strength between the electrode layer and the conductive resin layer was satisfactory, but since peeling did not occur, this was determined to be the occurrence of warping cracks.
[0152] In Example 3, when the average thickness of the silver (Ag) coating layer was formed to be less than 2 μm, warping cracks occurred in 3 of 20 sheets due to warping stress, and peeling occurred in 10 sheets, and there was no sheet with adhesion strength defect. Since the warping cracks occurred in the sheet where peeling did not occur, it was determined that the silver (Ag) coating layer was not properly formed.
[0153] In Example 4, when the average thickness of the silver (Ag) coating layer was formed to be 2 μm or more and 5 μm or less, no warping cracks or adhesion strength defects occurred due to the warping stress in 20 sheets, and peeling occurred in 20 sheets. Since the silver (Ag) coating layer was properly formed, it was determined to show excellent results in all the warping crack, peeling and adhesion strength evaluations.
[0154] In Example 5, when the average thickness of the silver (Ag) coating layer was formed to exceed 5 μm, no warping cracks were generated in 20 sheets due to the warping stress, and peeling occurred in 20 sheets, but there were two sheets with adhesion strength defects. Due to the excessive formation of the silver (Ag) coating layer, it was determined that the adhesion between the electrode layer and the conductive resin layer was weakened.
[0155] Next, Table 2 shows that, for each example, the warping crack, peeling, and adhesion strength were evaluated and reflected by changing the ratio L / IFL of the length L of the silver (Ag) coating layer of the belt portion to the length IFL of the electrode layer of the belt portion.
[0156] Example 6 is an example in which an electrode layer is formed on a ceramic body, a conductive resin layer is formed on the electrode layer, and a silver (Ag) coating layer is not formed. A sheet is manufactured by the same process as Example 1 except for the process of forming the silver (Ag) coating layer.
[0157] In Examples 7 to 10, except for changing the amount of silver nitrate (AgNO 3 ) aqueous solution to produce the length of the silver (Ag) coating layer differently, sheets were manufactured in the same manner as in Example 1. More specifically, the L / IFL in each sheet of Example 7 was about 30% (±5% error), the L / IFL in each sheet of Example 8 was about 50% (±5% error), the L / IFL in each sheet of Example 9 was about 70% (±5% error), and the L / IFL in each sheet of Example 10 was greater than 85%.
[0158] The evaluations of the warpage strength and the adhesive strength were performed in the same manner as in Table 1.
[0159] After evaluating the warpage strength and the adhesion strength, when even one sheet was defective during the adhesion strength evaluation, this was determined as ×, and even if there was no sheet with an adhesion strength defect, when any sheet among the 20 sheets had a warpage crack, or all 20 sheets were not completely peeled off, this was determined as a triangle (△), and among all 20 sheets, when peeling occurred without an adhesion strength defect or a warpage crack, this was determined as a circle (○).
[0160] Table 2:
[0161] Example Warping crack Stripping Adhesion strength Sure Example 6 5 / 20 5 / 20 0 / 20 △ Example 7 3 / 20 15 / 20 0 / 20 △ Example 8 0 / 20 20 / 20 0 / 20 O Example 9 0 / 20 20 / 20 0 / 20 O Example 10 0 / 20 20 / 20 2 / 20 X
[0162] In Example 6, since the silver (Ag) coating layer was not formed, warping cracks occurred in 5 of 20 sheets due to the warping stress, and peeling occurred in 5 sheets, and there was no sheet with adhesion strength defect. In Example 6, which is the same case as the conventional sheet in which the silver (Ag) coating layer was not formed, the adhesion strength between the electrode layer and the conductive resin layer was satisfactory, but since peeling did not occur, it was determined that this was the occurrence of warping cracks.
[0163] In Example 7, when the L / IFL of the sheet was formed to be about 30% (±5% error), warping cracks occurred in 3 of 20 sheets due to warping stress, and peeling occurred in 15 sheets, and no sheet with an adhesion strength defect occurred. Considering the occurrence of warping cracks in the sheet where peeling did not occur, it was determined that the silver (Ag) coating was not properly formed.
[0164] In Example 8, when the L / IFL of the sheet was formed to be about 50% (±5% error), there were no warping cracks or adhesion strength defects due to warping stress in 20 sheets, and peeling occurred in 20 sheets. Since the silver (Ag) coating was properly formed, it was determined that excellent results were shown in all evaluations of warping cracks, peeling, and adhesion strength.
[0165] In Example 9, when the L / IFL of the sheet was formed to be about 70% (±5% error), there were no warping cracks or adhesion strength defects due to warping stress in 20 sheets, and peeling occurred in 20 sheets. Since the silver (Ag) coating was properly formed, it was determined that excellent results were shown in all the evaluations of bending cracks, peeling, and adhesion strength.
[0166] In Example 10, when the L / IFL of the sheet was formed to exceed 85%, no warping cracks occurred due to warping stress in 20 sheets, and peeling occurred in 20 sheets, but there were two sheets with adhesion strength defects. Due to excessive formation of the silver (Ag) coating, it was determined that the adhesion between the electrode layer and the conductive resin layer was weakened.
[0167] Although the exemplary embodiments of the present disclosure have been described in detail above, the present disclosure is not limited to the above-mentioned embodiments and drawings, but is defined by the appended claims. Therefore, a person of ordinary skill in the art may make various substitutions, modifications or alterations without departing from the scope of the present disclosure defined by the appended claims, and these substitutions, modifications or alterations should be interpreted as being included within the scope of the present disclosure.
[0168] In addition, the expression "exemplary embodiment" used in the present disclosure does not mean the same embodiment, and is provided to emphasize and explain different unique characteristics. However, the embodiment presented above does not exclude the combination of features with another embodiment. For example, unless there is a description contrary to or contradictory to the item in another embodiment, even if the item described in a specific embodiment is not described in another embodiment, the item can also be understood as a description related to another embodiment.
[0169] In the present disclosure, these terms are only used to describe example embodiments and are not intended to limit the present disclosure. Unless the context clearly indicates otherwise, a singular form may also include a plural form.
Claims
1. A multilayer electronic component comprising: a body including a dielectric layer and inner electrodes alternately arranged with the dielectric layer in a first direction, the body including a first surface and a second surface opposite to each other in the first direction, a third surface and a fourth surface opposite to each other and connected to the first surface and the second surface in the second direction, and a fifth surface and a sixth surface opposite to each other in the third direction and connected to the first surface to the fourth surface; as well as an outer electrode including a connection portion provided on the third surface and the fourth surface and a band portion extending from the connection portion to a portion of the first surface and the second surface, wherein the outer electrode includes an electrode layer connected to the inner electrode and including a first conductive metal and glass, a conductive resin layer disposed on the electrode layer and including a second conductive metal and resin, and a silver coating layer disposed in the band portion and between the electrode layer and the conductive resin layer, The average thickness of the silver coating is greater than or equal to 2 μm and less than or equal to 5 μm.
2. The multilayer electronic component according to claim 1, wherein The silver coating is not provided in the connecting portion.
3. The multilayer electronic component according to claim 1, wherein: The average atomic percentage of silver in the silver coating layer is greater than or equal to 90 at %.
4. The multilayer electronic component according to claim 1, wherein: The average weight percentage of silver in the silver coating is greater than or equal to 95 wt %.
5. The multilayer electronic component according to claim 1, wherein When the length of the electrode layer of the belt portion is defined as IFL and the length of the silver coating layer of the belt portion is defined as L, 50%≤L / IFL is satisfied.
6. The multilayer electronic component according to claim 5, wherein: Meet L / IFL≤80%.
7. The multilayer electronic component according to claim 1, wherein: The first conductive metal and the second conductive metal are the same metal.
8. The multilayer electronic component according to claim 7, wherein: The first conductive metal and the second conductive metal are copper.
9. The multilayer electronic component according to claim 1, wherein: The external electrode further includes a plating layer disposed on the conductive resin layer.
10. A multilayer electronic component comprising: a body including a dielectric layer and inner electrodes alternately arranged with the dielectric layer in a first direction, the body including a first surface and a second surface opposite to each other in the first direction, a third surface and a fourth surface opposite to each other and connected to the first surface and the second surface in the second direction, and a fifth surface and a sixth surface opposite to each other in the third direction and connected to the first surface to the fourth surface; as well as an outer electrode including a connection portion provided on the third surface and the fourth surface and a band portion extending from the connection portion to a portion of the first surface and the second surface, wherein the outer electrode includes an electrode layer connected to the inner electrode and including a first conductive metal and glass, a conductive resin layer disposed on the electrode layer and including a second conductive metal and resin, and a silver coating layer disposed in the band portion and between the electrode layer and the conductive resin layer, The average atomic percentage of silver in the silver coating layer is greater than or equal to 90 at %.
11. The multilayer electronic component according to claim 10, wherein: The silver coating is not provided in the connecting portion.
12. The multilayer electronic component according to claim 10, wherein: When the length of the electrode layer of the belt portion is defined as IFL and the length of the silver coating layer of the belt portion is defined as L, 50%≤L / IFL is satisfied.
13. The multilayer electronic component according to claim 12, wherein: Meet L / IFL≤80%.
14. The multilayer electronic component according to claim 10, wherein: The first conductive metal and the second conductive metal are the same metal.
15. The multilayer electronic component according to claim 14, wherein The first conductive metal and the second conductive metal are copper.
16. The multilayer electronic component according to claim 10, wherein: The external electrode further includes a plating layer disposed on the conductive resin layer.
17. The multilayer electronic component according to claim 13, wherein: The silver coating is provided only in the band portion.
18. The multilayer electronic component according to claim 17, wherein: The average thickness of the silver coating is greater than or equal to 2 μm and less than or equal to 5 μm.
19. The multilayer electronic component according to claim 18, wherein: The silver coating includes a plurality of silver islands spaced apart from each other.
Citation Information
Patent Citations
Organic electroluminescent devices and electronic devices
KR1020230118092A